2017
DOI: 10.1155/2017/4378627
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Reveals Genes Mediating Salt Tolerance through Calcineurin/CchA-Independent Signaling inAspergillus nidulans

Abstract: Adaptation to changes in the environment is crucial for the viability of all organisms. Although the importance of calcineurin in the stress response has been highlighted in filamentous fungi, little is known about the involvement of ion-responsive genes and pathways in conferring salt tolerance without calcium signaling. In this study, high-throughput RNA-seq was used to investigate salt stress-induced genes in the parent, ΔcnaB, and ΔcnaBΔcchA strains of Aspergillus nidulans, which differ greatly in salt ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Based on phylogenetic analyses of the calmodulin gene, isolates of A. terreus cultured from marine/sea-related environments intermixed with those cultured from terrestrial habitats, suggesting that the marine isolates are not phylogenetically distinct [46,47]. The Aspergillus terreus isolate in this study may be of a terrestrial origin as the molecular mechanisms expressed towards salt tolerance (arginine biosynthesis, HOG, MAPK) are similar to those expressed by other terrestrial Aspergillus species, such as A. oryzae [43], A. nidulans [48], A. fumigatus [49] and A. montevidensis [50]. Aspergillus species have been shown to be able to tolerate a range of environmental stressors by their repertoire of stress-related genes [37,41,[49][50][51][52][53][54][55][56][57] and were found ubiquitous in deep-sea environments.…”
Section: Stress Response Of Aspergillus Terreus Ntou4989mentioning
confidence: 82%
“…Based on phylogenetic analyses of the calmodulin gene, isolates of A. terreus cultured from marine/sea-related environments intermixed with those cultured from terrestrial habitats, suggesting that the marine isolates are not phylogenetically distinct [46,47]. The Aspergillus terreus isolate in this study may be of a terrestrial origin as the molecular mechanisms expressed towards salt tolerance (arginine biosynthesis, HOG, MAPK) are similar to those expressed by other terrestrial Aspergillus species, such as A. oryzae [43], A. nidulans [48], A. fumigatus [49] and A. montevidensis [50]. Aspergillus species have been shown to be able to tolerate a range of environmental stressors by their repertoire of stress-related genes [37,41,[49][50][51][52][53][54][55][56][57] and were found ubiquitous in deep-sea environments.…”
Section: Stress Response Of Aspergillus Terreus Ntou4989mentioning
confidence: 82%
“…This protein is part of protein complex, which physically connect endoplasmatic reticulum and mitochondria. Wang et al (130) showed upregulation of this gene in Aspergillus nidulans under salinity stress.…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock proteins are a ubiquitous family of proteins involved in responses to many abiotic stresses, including heat, salinity, and oxidative stresses [43,44,45,46,47]. They are named by their molecular weight in kildodaltons and often serve as molecular chaperones, helping nascent and denatured peptides fold properly or be tagged for degradation.…”
Section: Discussionmentioning
confidence: 99%